Assessment of Ectoparasites and Heavy Metal Concentrations in Hemichromis Fasciatus, Liza Falcipinnis and Sarotherodon Galileus - Ikiriko N; Robert B; Amuzie C C (Newinera Publisher, 2020)
Ectoparasites and heavy metal pollution pose health risks to both wild and aquaculture fish species. Here, we examine the ectoparasites of fish species (Hemichromis fasciatus, Liza falcipinnis and Sarotherodon galileus) from Abalama and Ilelema locations of the Buguma Creek, Rivers State, Nigeria, over a period of six months (February to July, 2020). Fish tissues (muscles, gills and gut) were also examined for heavy metals (Cr, Cd and Pb). Parasitological investigations were done following standard procedures, as well as the heavy metal analysis which was done using atomic absorption spectrophotometer after dry ashing-acid digestion. Two ectoparasites were isolated: Zeylanicobdella arugamensis from L. falcipinnis at both locations and Cymothoa exigua from H. fasciatus at Ilelema. In surface water, Cr concentration was <0.003µg/l throughout the study period; Cd concentrations ranged between 0.06µg/l and 0.09µg/l at both locations, while Pb values were 0.29µg/l - 0.64µg/l at Abalama, and 0.56µg/l – 0.71µg/l at Ilelema. These values were within international acceptable standards. In fish tissues, however, Cr values were <0.003µg/g in both locations throughout the study period. At Abalama, Cd ranged between 7.18µg/g and 8.15µg/g, and Pb between 72.83µg/g and 92.23µg/g. At Ilelema, Cd concentrations were between 7.56µg/g and 8.67µg/g while Pb values ranged between 78.32µg/g and 92.88µg/g. Differences in heavy metal concentrations in both water and fish tissues between both locations were not statistically significant (p>0.05). All fish species and tissues bioaccumulated appreciable concentrations of the heavy metals. Cr in fish tissues was within permissible limits, but all Cd and Pb values exceeded international permissible limits.